Improved Characteristics of CdSe/CdS/ZnS Core-Shell Quantum Dots Using an Oleylamine-Modified Process - Kai-Ping Chang; Yu-Cheng Yeh; Chung-Jui Wu; Chao-Chun Yen; Dong-Sing Wuu (Nanomaterials, 2022)
CdSe/CdS with ZnS/ZnO shell quantum dots (QDs) are synthesized by a one-pot method with various oleylamine (OLA) contents. The crystal structures of the QDs were analyzed by X-ray diffractometry, which showed ZnS diffraction peaks. It was represented that the ZnS shell was formed on the surface of the CdSe/CdS core. Interestingly, QDs with a high OLA concentration exhibit diffraction peaks of ZnS/ZnO. As a result, the thermal stability of QDs with ZnS/ZnO shells exhibits better performance than those with ZnS shells. In addition, the photoluminescence intensity of QDs with ZnS/ZnO shells shows a relatively slow decay of 7.1% compared with ZnS shells at 85 °C/85% relative humidity aging test for 500 h. These indicate that QDs with different OLA modifications can form ZnS/ZnO shells and have good stability in a harsh environment. The emission wavelength of QDs can be tuned from 505 to 610 nm, suitable for micro-LED display applications.